Utilizing brown mushroom stem waste as an eco-friendly alternative to soybean meal in layer chick nutrition - Abdel-Wareth, Ahmed A. A.; Stamps, Kayla G.; Salahuddin, Md; Balan, Venkatesh; Mohammadi, Maedeh; Kim, Woo Kyun; Zhu, Weihang; Ahmed, Ahmed A.; Gray, Cassandra D.; Aviña, Adrian M. W.; Rounds-Carter, Taylor; Carr, Trahmilla; et al. (Frontiers in Veterinary Science, 2025)
ObjectivesThis study evaluated the potential of brown mushroom stem (BMS) powder as a sustainable feed ingredient in poultry diets by assessing its effects on growth performance, health status, and environmental impact. Specifically, the research investigated whether the partial replacement of soybean meal with BMS powder could maintain productive performance while improving physiological responses and, gas emission in Lohmann LSL Lite chicks.MethodsThe study involved 160 3-week-old Lohmann LSL Lite chicks. After a 4-day adaptation period on the control diet, the chicks were assigned to four dietary groups: 0% (control), 2%, 4%, and 6% BMS of replacing soybean meal. BMS was sourced from a local commercial mushroom producer. The stems were cleaned, washed, and freeze-dried to reduce their moisture content to below 5% by weight, ensuring extended shelf life. The freeze-dried BMS were then finely ground into powder for inclusion in the chicken feed. Each group consisted of five replicates, and each replicate had eight chicks. Feed intake (FI) and growth performance were recorded weekly over a 5-week duration in a cage system. Gas emissions from excreta were measured using a sensor-based system. At the end of the study, randomly selected birds were slaughtered for blood and organ collection for further analysis. Data analysis was performed using one-way ANOVA in SAS 9.4 software. Polynomial contrasts were used to analyze the linear and quadratic effects of increasing levels of BMS powder.ResultsThe results showed no significant (P < 0.05) differences in final body weight, weight gain, feed intake, and feed conversion ratio (FCR) among groups. Internal organ weight also showed no significant (P < 0.05) difference among groups, indicating the safety of BMS powder incorporation in chick diets. Blood biochemical parameters, including total protein, globulin, aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), uric acid, and cholesterol, exhibited both linear (P < 0.05) and quadratic (P < 0.05) effects with varying levels of BMS powder. Interestingly, gas emissions, including carbon dioxide (CO2), ammonia (NH3), and methane (CH4), measured on days 31 and 32 of the experiment, exhibited significant quadratic responses (P < 0.05) to increasing levels of BMS powder in the diet. While these effects were modest and limited to a short observation window, they suggest a potential short-term environmental benefit that warrants further investigation. These results indicate that BMS powder inclusion may positively influence certain biochemical markers and reduce the environmental footprint of poultry production.ConclusionBMS powder could be a potential and sustainable replacement for soybean meal in poultry diets. It maintained consistent growth performance and organ weight, reduced gas emissions, and positively influenced blood biochemical markers, emphasizing its potential benefits. Future research should validate these findings in commercial settings and explore their long-term applications for broader adoption in eco-friendly production systems.